Gastrointestinal Symptoms in Marfan Syndrome and Hypermobile Ehlers-Danlos Syndrome - N. Inayet; J. O. Hayat; A. Kaul; M. Tome; A. Child; A. Poullis (Gastroenterology Research and Practice)
Objective. Marfan syndrome (MS) is a multisystem disorder caused by a mutation in FBN1 gene. It shares some phenotypic features with hypermobile Ehlers-Danlos syndrome (EDS) such as joint hypermobility. EDS is a group of inherited heterogenous multisystem disorders characterized by skin hyperextensibility, atrophic scarring, joint hypermobility, and generalized tissue fragility. Hypermobile EDS (hEDS) is thought to be the most common type. Recent studies have suggested an association between connective tissue hypermobility and functional gastrointestinal disorders (FGDs). The aim of this study is to determine the prevalence of gastrointestinal symptoms in patients with Marfan syndrome and hypermobile EDS. Method. Patients with a diagnosis of either MS or hEDS attending cardiology or rheumatology outpatients at our hospital were asked to complete SF36 RAND and Rome IV Diagnostic questionnaires. Questionnaires were also completed by patients who are members of Marfan Association UK. The same questionnaires were also completed by age- and gender-matched controls attending fracture clinic without existing diagnoses of MS or hEDS. Results. Data were collected from 45 MS patients (12 males and 33 females, age range 19–41 years, mean 28 years) and 45 hEDS patients (6 males and 39 females, age range 18–32 years, mean 24 years). None had a previous organic gastrointestinal diagnosis. The control group was matched for age and sex (18 males and 72 females, age range 18–45, mean 29 years). Both MS and hEDS groups showed a higher prevalence of abdominal symptoms compared to the control group; however, the hEDS group not only showed a higher prevalence but more frequent and severe symptoms meeting Rome IV criteria for diagnosis of FGIDs. Nearly half of the hEDS patients met the criteria for more than one FGID. The hEDS group also scored lower on quality of life (QOL) scores in comparison to either of the other groups with a mean score of 48.6 as compared to 54.2 in the Marfan group and 78.6 in the control group. Conclusion. FGIDs are reported in both Marfan syndrome and hypermobile Ehlers-Danlos syndrome but appear to be more common and severe in hEDS. These patients score lower on quality of life scores as well despite hypermobility being a common feature of both conditions. Further work is needed to understand the impact of connective tissue disorders on gastrointestinal symptoms.